Gambaran Kejadian Kematian Ibu di Kabupaten Grobogan, Jawa Tengah Tahun 2016-2018 - Nimas Puspitasari; Mateus Sakundarno Adi (FORIKES, 2021)
Grobogan District is the biggest contributor to maternal mortality cases in Central Java. Maternal Mortality Rate in Grobogan District increased again in 2018 by 152.5 per 100,000 live births. The purpose of this research is to analyze the description of the incidence of maternal mortality in Grobogan District in 2016-2018. This research was a descriptive study using secondary data of Maternal Verbal Autopsy (OVM) on maternal mortality at the Grobogan District Health Office from 2016-2018. The results of this study indicated that the majority of maternal mortality occurred at the age of 20-35 years (77.9%), mothers with primary education (42.9%), during childbirth (66.2%), hypertension (39.0%), death unknown (40.3%), hospital (85.7%). The results of this study are expected to be used as material in determining the direction of maternal health program policies in Grobogan District. Suggestions in this study are the need for early recognition of the pregnancy period, and the puerperium and increase alertness to pregnancy complications. Keywords: maternal mortality; Grobogan District ABSTRAK Kabupaten Grobogan merupakan penyumbang terbesar kasus kematian ibu di Jawa Tengah. Angka Kematian Ibu di Kabupaten Grobogan kembali meningkat di tahun 2018 sebesar 152,5 per 100.000 kelahiran hidup. Tujuan penelitian ini untuk menganalisis gambaran kejadian kematian ibu di Kabupaten Grobogan tahun 2016-2018. Penelitian ini merupakan penelitian deskriptif yang menggunakan data sekunder Otopsi Verbal Maternal (OVM) kematian ibu yang ada di Dinas Kesehatan Kabupaten Grobogan dari tahun 2016-2018. Hasil penelitian ini menunjukkan bahwa mayoritas kematian ibu terjadi pada usia 20-35 tahun (77,9%), ibu berpendidikan SD (42,9%), saat nifas (66,2%), hipertensi (39,0%), waktu kematian tidak diketahui (40,3%), Rumah Sakit (85,7%). Hasil penelitian ini diharapkan dapat dijadikan bahan dalam penentuan arah kebijakan program kesehatan maternal di kabupaten Grobogan. Saran dalam penelitian ini adalah perlunya pengenalan secara dini mengenai masa kehamilan, dan masa nifas serta meningkatkan kewaspadaan terhadap komplikasi kehamilan. Kata kunci: kematian ibu; Kabupaten Grobogan